Comparative evaluation of stress generation in primary teeth restored with zirconia and BioFlx crowns: A finite element analysis - Deolikar, Sayali; Rathi, Nilesh; Mehta, Vini (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Maintaining the functional integrity of primary teeth is important, as these teeth are integral in vital functions such as mastication, speech development, and space maintenance for permanent teeth; hence, premature loss of primary teeth can affect a child's quality of life. Various restorative materials are available to restore the function of grossly decayed teeth. Stainless steel crowns and zirconia crowns are widely used in pediatric dentistry; however, there are certain disadvantages associated with these materials. Recently introduced BioFlx crowns provide acceptable esthetics with a conservative approach. Nevertheless, there is a lack of evidence regarding their strength and clinical acceptability. Finite element analysis measures the physical response of teeth and assesses the stress generation, which is important to estimate the integrity of the restorations and crowns. Purpose: The aim of this in vitro study was to evaluate and compare stress generation in primary teeth restored with zirconia and BioFlx crowns using finite element analysis. Methods: Models of extracted teeth restored with zirconia and BioFlx crowns were used for the study. The finite element analysis of these models was carried out through Analysis of Systems (ANSYS) software. The models were subjected to a simulated occlusal loading force of 245 N. Results: Von Mises stress generated in BioFlx crowns along with underlying dentin was much less compared to that which was generated in zirconia crowns. Conclusion: Restoring the functional integrity of carious teeth is essential. BioFlx crowns can be used as full coverage restorations and can be a suitable alternative to zirconia crowns and traditional stainless steel crowns.